HIV/AIDS in Vancouver, British Columbia: a growing epidemic - Lima Viviane D; Tyndall Mark W; Gilbert Mark; Harvard Stephanie S; Druyts Eric; McInnes Colin W; Wood Evan; Montaner Julio SG; Hogg Robert S (Harm Reduction Journal, 2009)
Abstract The prevalence of HIV in Vancouver, British Columbia was subject to two distinct periods of rapid increase. The first occurred in the 1980s due to high incidence among men who have sex with men (MSM), and the second occurred in the 1990s due to high incidence among injection drug users (IDU). The purpose of this study was to estimate and model the trends in HIV prevalence in Vancouver from 1980 to 2006. HIV prevalence data were entered into the UNAIDS/WHO Estimation and Projection Package (EPP) where prevalence trends were estimated by fitting an epidemiological model to the data. Epidemic curves were fit for IDU, MSM, street-based female sex trade workers (FSW), and the general population. Using EPP, these curves were then aggregated to produce a model of Vancouver's overall HIV prevalence. Of the 505 000 people over the age of 15 that reside in Vancouver, 6108 (ranging from 4979 to 7237) were living with HIV in the year 2006, giving an overall prevalence of 1.21 percent (ranging from 0.99 to 1.43 percent). The subgroups of IDU and MSM account for the greatest proportion of HIV infections. Our model estimates that the prevalence of HIV in Vancouver is greater than one percent, roughly 6 times higher than Canada's national prevalence. These results suggest that HIV infection is having a relatively large impact in Vancouver and that evidence-based prevention and harm reduction strategies should be expanded.